Sistem Penyiaran Broadcasting Programa 1 (91.2 Fm) di Radio Republik Indonesia Jakarta Pusat - Ester Risanis Travelya; Desmira Desmira (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Radio is a mass media that is still used by many people as a means of communication, such as listening to songs, informing news and others. One of the radio stations that still exists and is developing to this day is Radio Republik Indonesia, which is overseen by the government, which can now be accessed via available radio and websites so that it makes it easier for listeners to listen to and watch the news and can be accessed anywhere. The author conducted research at Radio Republik Indonesia in the Central Jakarta section using qualitative research methods where the author went directly to the field or observed and interviewed as well as assisting with literature studies. The aim of conducting this research was to find out how the broadcasting system and radio supporting equipment at Radio Republik Indonesia Jakarta . So the results obtained are in the form of a radio broadcasting system at Radio Republik Indonesia using two broadcasting systems, namely audio and visual as well as supporting equipment used in the form of Microphones, Mixers, OB – Van, MCR, Transmitter, STL and Antenna.